Α-Na2Ni2Fe(PO4)3: a dual positive/negative electrode material for sodium ion batteries1. Issue 10 (14th March 2015) - Essehli, R.; Belharouak, I.; Ben Yahia, H.; Chamoun, R.; Orayech, B.; El Bali, B.; Bouziane, K.; Zhou, X. L.; Zhou, Z.
<x xml:space="preserve">Abstract</x> The low temperature polymorph of Na2Ni2Fe(PO4)3, crystallizing with a stuffed α-CrPO4-type structure, plays a dual anode/cathode behaviour.